Application of Solvent Evaporation to Generate Supersaturated Lipid-Based Formulations: Investigation of Drug Load and Formulation Quality - Felix Paulus; Jef Stappaerts; Annette Bauer-Brandl; Dirk Lauwers; Liesbet Smet; Eline Hermans; René Holm (Pharmaceutics)
Background/Objectives: Lipid-based formulations (LBFs) are enabling formulations for poorly water-soluble, mostly lipophilic drugs. In LBFs, the drug is pre-dissolved in the formulation which can consist of lipids, surfactants, and/or cosolvents. In cases where the administration of high amounts of a drug is required, exceeding the drug solubility in the lipidic vehicle at the administration temperature, supersaturated LBFs are an option. The standard method described in the literature for inducing supersaturation in LBFs is to dissolve the drug substance in the lipidic vehicle at an elevated temperature, e.g., at 60 °C, and then subsequently let the formulation cool to ambient temperature before administration (heat-based approach). In this work, an alternative approach to induce supersaturation in LBFs was investigated in order to evaluate if higher drug loads, i.e., the concentration of drug dissolved in the vehicle, could be reached compared to the loading obtainable via heating. Methods: A volatile solvent that is miscible with the lipid matrix and in which the compound has a high solubility is added to the lipid matrix, after which the solvent is evaporated. Both approaches were compared in this work investigating two different LBFs loaded with the BCS-class II drugs celecoxib and fenofibrate. Results: When inducing supersaturation by heat, drug loads of 238% for celecoxib and 278% for fenofibrate could be achieved relative to the solubility at ambient temperature. Using the solvent-based approach, drug loads of up to 475% for celecoxib and 557% for fenofibrate could be prepared in the LBFs using dichloromethane (DCM) as the volatile solvent. However, those highly supersaturated preparations showed suboptimal physical stability and quickly led to precipitation when the LBFs were stored at ambient temperature. In addition, selected formulations were analyzed with GC-headspace to determine the residual DCM after solvent evaporation using a vacuum evaporator. This analysis revealed that the DCM content exceeded regulatory requirements, with up to 21,883 ppm DCM in the formulations. Conclusions: Overall, the relatively high residual DCM concentration and the suboptimal physical stability do not make the approach easily usable for generating supersaturated lipid-based formulations.